2011 International Conference on Power and Energy Systems 2011
DOI: 10.1109/icpes.2011.6156657
|View full text |Cite
|
Sign up to set email alerts
|

Linear programming approach for state estimation incorporating phasor measurements

Abstract: This paper presents methodologies for incorporating phasor measurements into conventional state estimator. The angle measurements obtained from Phasor Measurement Units are handled as angle difference measurements rather than incorporating the angle measurements directly. Handling in such a manner overcomes the problems arising due to the choice of reference bus. Current measurements obtained from Phasor Measurement Units are treated as equivalent pseudo-voltage measurements at the neighboring buses. Two solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Also, the gain matrix tends to become ill-conditioned as the system size increases. To overcome the numerical problems associated with SCADA based SEs, several techniques, like Peters and Wilkinson method [6], orthogonal decomposition [7,8], Levenberg-Marquardt algorithm [9], linear programming [10], and regularization method [11] have been explored by researchers. Approximate expres-sion for the condition number of the gain matrix was formulated in [6] and [12], and it was found that the injection measurements caused degradation in the numerical performance of the SE.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the gain matrix tends to become ill-conditioned as the system size increases. To overcome the numerical problems associated with SCADA based SEs, several techniques, like Peters and Wilkinson method [6], orthogonal decomposition [7,8], Levenberg-Marquardt algorithm [9], linear programming [10], and regularization method [11] have been explored by researchers. Approximate expres-sion for the condition number of the gain matrix was formulated in [6] and [12], and it was found that the injection measurements caused degradation in the numerical performance of the SE.…”
Section: Introductionmentioning
confidence: 99%